Spectroscopic and chromatographic fingerprint analysis of composition variations in Coffea arabica leaves subject to different light conditions and plant phenophases - Delaroza,Fernanda (2014)
Fingerprints of self-shaded and sunlight-exposed leaves of the same Coffea arabica plant were obtained to determine metabolic concentration changes owing to different light environments and phenological stages. Leaf extract yields of the ethanol, acetone, dichloromethane and hexane solvents, as well as their statistical design mixtures, are reported. Highest yields are obtained with binary 1:1 ethanol-acetone mixtures for all sun-exposed and self-shaded leaves. Principal component analysis (PCA) of Fourier transform infrared (FTIR) spectra of leaf extracts indicate spectral differences between 2962-2828, 1759-1543 and below 1543 cm-1 that can be attributed to higher concentrations of fatty acid esters or the ester group in triglycerides, caffeine, chlorogenic acids and carbohydrates that are more prevalent in leaves of flowering plants. High-performance liquid chromatography with UV diode array detector (HPLC-UV-DAD) spectra of the chromatographic peaks for the extracts showed that sun-exposed samples contain stronger absorptions for caffeine, chlorogenic acid and theobromine. Confirmatory experiments carried out with reference UV calibration curves determined caffeine contents for sun-exposed leaves that are about double those for self-shaded leaves of flowering plants. Knowledge of leaf caffeine content in Coffea arabica is of ecological importance since sun-exposed conditions seem more stressful than self-shading ones for this species. Lipid concentrations in self-shaded leaves are almost double those that were sun-exposed.